Superhydrophobicity: Superhydrophobic Vertically Aligned Carbon Nanotubes for Biomimetic Air Retention under Water (Salvinia Effect) (Adv. Mater. Interfaces 13/2017). Issue 13 (July 2017) - Babu, Deepu J.; Mail, Matthias; Barthlott, Wilhelm; Schneider, Jörg J.
Abstract : Persistent air layer retention under water ( Salvinia effect ) is a result of a complex hierarchical structuring of surfaces. Besides providing an impressive silvery appearance it may serve various ecological functions like fluid drag reduction, respiration (plastron effect), sensing and camouflage. In article number1700273, Jörg J. Schneider, Wilhelm Barthlott, and co‐workers report the Salvinia effect observed on superhydrophobic vertically aligned carbon nanotubes. This may pave the way for the development of future biomimetic sensor systems.